Role of Elementary Teachers in Providing Guidance and Counseling Services at Muhammadiyah 8 Elementary School in Malang City - Kusumaningtyas, Dian Ika; Kumalasani, Maharani Putri; Deviana, Tyas (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2019)
The role of the professional teacher in addition to teaching the teacher also acts as an educator or mentor. Guidance provided should be set forth in guidance and counseling services that accommodate the role of the teacher as a mentor. Important teachers have insights and knowledge related to guidance and counseling. So that assistance is needed regarding guidance and counseling services. The method used in this service is a Workshop on the Role of Elementary Teachers as Counselors, Assistance in problem analysis and preparation of Guidance and Counseling programs, Implementation of Guidance and Counseling program preparation, Reflection and follow-up. The results of this service resulted in the design of a guidance and counseling program that had been made by each class teacher based on an analysis of the conditions of learning and school conditions. The guidance and counseling programs that have been prepared include orientation services, information services, placement services, learning services, individual counseling services, and group guidance services.